Green Human Resource Management and Its Impacts on Competitive Advantages in Private School - POR, Narith; KHLOK Thavan (MASI Mandiri Edukasi, 2024)
Industry growth and technological advancement have increased concerns about the environment. These concerns require companies to adopt environmental practices in their business operations. Green practices in human resources are important. However, there was no study on environmental adoption in human resources in Cambodia. The research aims to assess the extent of green human resource management practices and the relationship between these practices and competitive advantages. Researchers randomly selected a total of 100 teachers from private schools in Siem Reap province, Cambodia, for interviews. A Likert scale ranging from 1 to 5 was used in this research, with 1 indicating